Principals' Facilities Maintenance Measures and Administrative Effectiveness in Private Secondary Schools in Kwara State, Nigeria - Olaifa, Adeseko Sunday; Ali, Mariam Adetola Arogundade; OLAIFA, Ebunlomo Oreoluwa; OLADIMEJI, Rasheedat Modupe; AKPALA, Kingsley Chigozie (Chalim Journal of Teaching and Learning, 2024)
Maintaining physical infrastructure in private secondary schools is particularly critical because these institutions operate in a highly competitive environment where their reputation is tied to academic performance and the quality of their facilities. This study investigated the relationship between principals' facilities maintenance measures and administrative effectiveness in private secondary schools in Kwara State, Nigeria. The study was guided by two research questions and four research hypotheses. The descriptive survey of the correlational type was adopted for the study. The population of this study comprised 7,869 senior secondary school teachers. A sample of 250 teachers was selected using purposive and simple random sampling techniques. A researcher-designed instrument titled "Principals' Facilities Maintenance Measures and Administrative Effectiveness Questionnaire (PFMMAEQ) was utilised for data collection. The findings of this study revealed that principals in private secondary schools in Kwara State implement preventive, corrective, and emergency maintenance measures for their facilities. Similarly, the level of administrative effectiveness in private secondary schools in Kwara State is high. There is a significant relationship between principals' facilities maintenance measures and administrative effectiveness in private secondary schools in Kwara State. It was recommended that principals establish a comprehensive facilities maintenance framework that integrates preventive and emergency maintenance measures for consistent and effective management of school facilities. Principals should maintain a high level of administrative effectiveness by engaging in continuous professional development and fostering collaboration among school staff to enhance decision-making and operational efficiency.